Comparative analysis of peach and nectarine cultivars based on their ecological and biological indicators - Surányi, D. (International Journal of Horticultural Science, 2020)
Natural conditions other than the ecological conditions of the Chinese gene center (as 34-38° latitude and 600 to 2400 m above sea level), mainly dry subtropical, i.e. Mediterranean effects, facilitated the development of new forms and varieties (Scorza & Okie, 1991; Faust & Timon, 1995). Probably the primary cause of nectarines, this could also be the primary cause of mutations (probably about 2000 years ago) (Roach, 1985; Surányi, 1985). During the long domestication of peaches, its natural occurrence increased, which was greatly enhanced by its ecological and mutational ability and the organoleptical values of its fruit (Hedrick, 1917; Roach, 1985; Scorza & Okie, 1991; Faust et al., 2011). Through the Ellenberg-Borhidi model and its refinement, the author has demonstrated the suitability of peaches in a broad climate zone based on the relative ecological and biological values of 700 varieties. Among the varieties, clone cultivars and hybrids were Hungarian selected and crossed form, because the diverse environmental conditions of the Carpathian Basin and the past and present size of cultivation were representative (Faust & Timon, 1995; Timon, 2000). It can be concluded from the present relative ecological data that the average standard deviation is below 12% for both peach and nectarine varieties, but the relative biological values were very different. Comparison of cultivars or classical (downy) peaches (n = 562) and nectarines (n = 138) in terms of environmental values confirmed the difference in heat demand and salt tolerance of the two groups of varieties. The pictures of the paper also demonstrated the rich diversity of this fruit species, and after analyzing the apricot and plum varieties (Surányi 2014, 2018), the peculiarities of the relative ecological and biological values of peaches were confirmed.